THE IMPLEMENTATION OF UNLIMITED COMMUNICATION INFORMATION COMMUNICATION AND EDUCATION PROGRAM FAMILY PLANNING (KELUARGA BERENCANA A.K.A KB) IN THE ERA OF HARYONO SUYONO’S LEADERSHIP - Prasetya Yoga Santoso; Novalia Agung Wardjito Ardhoyo; Nasrullah Kusadjibrata; Mochammad Muminto Arief; Catur Priyadi; Adiella Yankie Lubis; Suharto, Suharto (International Journal of Social Science, 2024)
Every communication program has a strategy to ensure its success. As is the case with the Family Planning (Keluarga Berencana a.k.a KB) communication program initiated in the Haryono Suyono era. The program has become a spotlight in the world that Indonesia is able to control the birth rate. The purpose of this paper is to find out what the implementation of the Haryono era family planning communication program looks like, how it is evaluated, and if it is implemented in the current era, is it possible. The data collection method uses direct interview techniques. Thus, this paper uses a qualitative approach. It can be concluded that the implementation of the family planning program run by Haryono Suyono uses 3 (three) principles, namely (1) forming and maintaining a personal and humanist communication network, (2) setting and maintaining communication targets through simple messages, (3) the time dimension. Communicators need to maintain their reputation and have the authority and support to carry out family planning communication programs. Thus, the implementation of the program can be efficient and effective.